Synthesis of the augmented proportional navigation with lead bias aim point adapted to target for self-guided infrared missile - Đoàn Văn Thúy (Journal of Military Science and Technology, 2022)
The paper presents the research results of augmented proportional navigation with taking into account a lead bias command aim point adapted to target for an infrared self-guided surface to air missile. The lead bias command in the terminal phase is proposed to engage the target kill probability. Simulation studies have demonstrated outstanding advantages of the proposed guidance law is compared with pure proportional navigation guidance.